Translating the Biology of Diffuse Large B-cell Lymphoma Into Treatment. (24th January 2022) - Danilov, Alexey V; Magagnoli, Massimo; Matasar, Matthew J
Abstract: Diffuse large B-cell lymphoma (DLBCL) is characterized by clinical and molecular heterogeneity; however, this heterogeneity is rarely taken into account by standard-of-care treatment approaches. While the disease was traditionally classified based on transcriptome signatures purporting the tumor cell of origin, recent classification systems have further differentiated these subtypes into clusters based on molecular and genetic features. Alongside a better understanding of the biology of the disease and the signaling pathways involved, emerging therapeutic agents may be better aimed at attacking distinct disease subsets. It is hoped that molecular subtyping at diagnosis will allow patients to be allocated to the appropriate treatment that targets their specific disease subtype, thus advancing the promise of precision medicine in lymphoma, an approach that is most needed. For high-risk disease subsets, this is particularly important, and much research is still needed to develop agents effective in this population. Here, we review recent advances in DLBCL biology and how they can be translated into clinical care. Abstract : This article reviews recent advances in the biology of diffuse large B cell lymphoma and how to translate into better management of the heterogenous disease.